INFEKSI OPORTUNISTIK PADA ODHA (ORANG DENGAN HIV/AIDS) TERHADAP KEPATUHAN MINUM ARV (Anti Retroviral) DI KOTA PALEMBANG (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2020)
ABSTRACT Background : Human immunodeficiency virus (HIV) is a virus that damages the immune system and CD4 cells. The stronger the virus in destroying CD4 cells, the body has a higher risk for various types of infections and some cancers. There is no cure for HIV / AIDS, but there are several drugs that can reduce or inhibit the multiplication of HIV in the body with antiretroviral therapy (ARV). Opportunistic infections (OI) are the leading cause of death in 90% of people living with AIDS (Acquired Immunodeficiency Syndrome). The massive increasing number of death from opportunistic infections contributes to AIDS. The purpose of this study was to analysis the relationship of oportunitical infections in PLWHA on arvs compliance within palembang city Method : This research was an observational study, with a cross sectional study design on februari until maret 2020. Data samples of 235 People with Hiv and Aids (PLWHA) in Palembang were chosen by purposive random sampling. Results:The results showed that the proportion of adherence ARV in Palembang was 83%. respondents found 83% were male, age ranged between age 26-45 years as much as 72.3% with the most high school education 48.9%, entrepreneurs 34.5% and 54% are single. There is no significant relationship between opportunistic infections (OIs) experienced by PLWHAs against ARV compliance in the city of Palembang with (Pvalue 0.381;OR:0,675;95%CI: 0.328-1.392). There are as many as 62% of PLWHA who have comorbidities in the form of pulmonary TB out of all who have OIs Conclution :opportunitis infections (OIs) are not associated with ARV compliance, pulmonary tuberculosis is an opportunitis infection that was found in many of these studies Keyword : relationship; adherence; antiretroviral; ARV; HIV;AIDS; oportunitis infections; IO; pulmonary TB